A literatura como crítica social em sala de aula: uma leitura de Quarto de despejo, de Carolina Maria de Jesus - Andrade, Káren Aparecida de Sousa (2023)
The present research, of an interventional nature, is within the scope of literary literacy. As corpus, it is intended to work with the book Child of the dark: diary of Carolina Maria de Jesus, a memorial work published in 1960 by the Brazilian writer Carolina Maria de Jesus, knowing that it is a literary work that is not part of the school and academic literary canon, but which proves to be necessary as an item of the democratization of culture, even more if the public school context is considered. What motivates this research is the work with the memorialistic genre, due to its empathetic appeal, which invites students to read it, considering as target audience female and male students of the 9th grade of junior high school. As theoretical support for this study, it will be used the Greimasian semiotics, more specifically, the Tensive semiotics proposed by Claude Zilberberg with the developments proposed by the studies of Mariana Luz Pessoa de Barros, creator of the concepts of the past-event memory and the event memory. With this theoretical foundation, it was produced, applied to the stages of the work with literary texts proposed by Rildo Cosson and the contribution of the Law n. 9.394/96 with its normative derivatives, particularly the National Common Curricular Base, as a didactic-pedagogical tool, a notebook intended for the aforementioned student body, but with the possibility of adaptations for other grades, accompanied by instructions on application procedures for teachers who work at the elementary level – final years.